2005
DOI: 10.1083/jcb.200505035
|View full text |Cite
|
Sign up to set email alerts
|

Cellular basis of urothelial squamous metaplasia

Abstract: Although the epithelial lining of much of the mammalian urinary tract is known simply as the urothelium, this epithelium can be divided into at least three lineages of renal pelvis/ureter, bladder/trigone, and proximal urethra based on their embryonic origin, uroplakin content, keratin expression pattern, in vitro growth potential, and propensity to keratinize during vitamin A deficiency. Moreover, these cells remain phenotypically distinct even after they have been serially passaged under identical culture co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 61 publications
3
47
0
Order By: Relevance
“…This is in contrast with the absence of bladder tumors upon Rb1 ablation in the urothelium (13). In this regard, we did not observe bladder tumor development in large cohorts of mice bearing the specific elimination of Rb gene directed by keratin K14cre expression (14), which is active in the adult mouse urothelium (15), even in the absence of p107 (16), E2F1 (17) or p130 (18). These data indicate the existence of large overlapping roles for the Rb family members in bladder urothelial cells, similar to the reported for other mouse epithelial cells (19).…”
Section: Introductionmentioning
confidence: 69%
“…This is in contrast with the absence of bladder tumors upon Rb1 ablation in the urothelium (13). In this regard, we did not observe bladder tumor development in large cohorts of mice bearing the specific elimination of Rb gene directed by keratin K14cre expression (14), which is active in the adult mouse urothelium (15), even in the absence of p107 (16), E2F1 (17) or p130 (18). These data indicate the existence of large overlapping roles for the Rb family members in bladder urothelial cells, similar to the reported for other mouse epithelial cells (19).…”
Section: Introductionmentioning
confidence: 69%
“…Thus, the Wolffian ducts have been shown to undergo apoptosis during ureteral transposition and therefore do not contribute to trigone formation (7). Instead, a number of recent mouse models and tissue-transposition studies (7, 8), as well as in vitro studies of urothelial cells (9), suggest that the trigone is endodermal in origin. In males, the bladder base rests on the endopelvic fascia and the pelvic floor musculature, and the bladder neck is 3 to 4 cm behind the symphysis pubis and is fixed by the endopelvic fasciae and the prostate.…”
Section: Normal Anatomy and Physiology Of The Urinary Tractmentioning
confidence: 99%
“…Although the term urothelium has been used to describe the epithelia covering the mucosal surfaces of the bulk of the urinary tract, which share the expression of a group of integral membrane proteins called uroplakins, recent data indicate that the urothelia of the ureters, bladder, and possibly other areas are distinguishable with respect to the detailed morphological and biochemical features, their in vitro proliferative behaviors when placed under identical tissue-culture conditions, and their embryological origin. For example, it has been shown that ureteral urothelium contains lower amounts of uroplakins and fewer cytoplasmic fusiform vesicles than bladder urothelium (9, 14, 15). It is now clear that these phenotypic differences are due to intrinsic divergence instead of extrinsic modulation (9).…”
Section: Normal Anatomy and Physiology Of The Urinary Tractmentioning
confidence: 99%
See 2 more Smart Citations